Behavior of RC stepped beams with different configurations: An experimental and numerical study. (9th September 2020) - Fayed, Sabry; Basha, Ali; Elsamak, Galal
Abstract: In the current research, an experimental program, consisting of one straight beam and seven stepped beams (SBs), is to be carried out. Furthermore, a numerical validation is to be applied using finite element analysis. The effect of the additional vertical and horizontal stirrups, the diagonal bars, the configuration of the tension bars, and the inclination angle of the stepped joint on the behavior of the SB is to be examined. Moreover, the influence of the width and the drop of the stepped joint on the behavior of the SB is to be induced. Compared with the straight beam, the ratios of the ultimate load decrease of the SB ranged from −64.23% to 0.00%. On the one hand, as the joint drop increases, the ultimate load of the SB decreases. On the other hand, when the joint width increases, the ultimate load of the SB increases. Many proposed techniques in reinforcing and dimensions of the stepped part have increased the flexural capacity. Proposed equations of the flexural capacity of the SB are to be induced after examination, taking into consideration the required parameters of the stepped beams, such as the compressive strength of the concrete, the tension and the compression steel, the dimension of the beam section, the horizontal stirrups, the diagonal bars, or the width and the drop of the stepped joint.